Improving Learning Motivation and Cognitive Learning Outcomesusing Blended Learning-Based Guided Inquiry Strategy Through Lesson Study in Genetics - . Waris; Herawati Susilo (Bandar Lampung University (UBL), 2014)
There are still problems in the teaching and learning processes in Biology Department, Faculty of Mathematics and Science Education, Teacher Training College PGRI Jember. Most of the lectures are still conducted through face to face meeting, unidirectional and low participation of students. Therefore, the students’ motivation and cognitive learning outcomes are also still not as expected. There are also lack of sharing among lecturers in planning the teaching and learning processes, and the use of multimedia information technology is not maximized. This research aims to improve the motivation and cognitive learning outcomes of the students with different academic capabilities by using Blended Learning-based guided inquiry strategy through Lesson Study in Genetics Course. The subjects were 54 biology education students of the Teachers Training College PGRI Jember who attended genetics course. The subjects were divided into two groups, which are lower academic group and higher academic group. The indicator of improvement was determined by the increase of percentage (%) in motivation and cognitive learning outcomes before and after the learning processes.The results showed that the increase of motivation to learn in the lower academic capability students was 29.61%. This was higher than the increase of motivation to learn in the higher academic capability students which was 25.35%. The increase of cognitive learning outcomes in the lower academic capability students was 95.86%. This was also higher than the increase of cognitive learning outcomes in the higher academic capability students which was 81.16%. The increase in all aspects happened because by using the Blended Learning-based guided inquiry strategy, the students could search for and found their own concepts of genetics by using information technology. The Lesson Study has improve the lecturers’ awareness of the need to share experience among lecturers to improve their experties in conducting a higher quality of teaching learning processes.